What is Blockchain? : a user-friendly guide for the enterprise - Hargrave, John; Karnoupakis, Evan (O'Reilly Media, 2019)
Everyone's talking about blockchain. This exciting technology has the potential to impact our lives in much the same way as the internet did, but few understand how it actually works. Written for business technology leaders, this report breaks down the complexity of blockchain into plain language and simple illustrations so you can easily explain it to your colleagues. Sir John Hargrave and Evan Karnoupakis go beyond the hype to help you discover valuable opportunities for using blockchain in your business. The practical examples in this report will inspire you to get started on your own project; the real-world lessons will ensure you get it right. Understand the building blocks of blockchain, including the decentralized ledger, nodes, consensus protocols, and smart contracts Get up to speed on basic blockchain concepts, such as mining, forking, governance, and regulation Learn the power of the Blockchain Network Effect, the mystery of the Consensus Paradox, and other key blockchain principles Discover the challenges to setting up a blockchain project, plus four simple best practices to succeed.